Die Netzneutralitätsdebatte aus ökonomischer Sicht - Thomas Fetzer; Martin Peitz; Heike Schweitzer (Wirtschaftsdienst, 2012)
Unter dem Stichwort 'Netzneutralität' wird in Öffentlichkeit und Politik zur Zeit intensiv diskutiert, welchen Anforderungen die Datenübertragung in Telekommunikationsnetzen künftig genügen muss. Dabei stellt sich die Frage, ob Daten priorisiert werden dürfen und wenn ja, in welchem Ausmaß dies geschehen soll. – – Net neutrality has become a hot topic in politics and among the general public in Europe, even if different people attach different meanings to this term. The central questions are as follows: Which requirements must be met when transmitting data in telecommunication networks, in particular with respect to pricing and prioritising certain content? To what extent and in which way, if at all, is regulatory intervention currently called for? This article introduces central issues and discusses the economics of net neutrality. In particular, it elaborates on the complex interaction between decisions made by content providers and those made by network operators.
Keywords: L13; L51; 330; Internet; Netzzugang; Regulierung